Understanding benchmarking / Haron Wee Ah Boo - Wee Ah Boo, Haron (Perpustakaan Tun Abdul Razak, UiTM, 2004)
This article defines benchmarking, briefly explains the types of benchmarking, and blends a description of its processes.